Puzzle dan Braille Lontara Sebagai Upaya Pelestarian Bahasa Daerah Terhadap Tunanetra di Kota Makassar - Bustan Bustan; Jumadi Jumadi; Bahri Bahri; Ahmadin Ahmadin; Asmunandar Asmunandar (Universitas Negeri Makassar, 2024)
Visually impaired people are still often the object of physical violence and discrimination in society, because they consider that the visually impaired are a separate part, not part of a society or as citizens. The discriminatory attitude towards the blind and the lack of facilities led to a strong bond and led to the formation of a community for the blind. Persatuan Tunanetra Indonesia (PERTUNI) as a pioneer who fights for the rights of blind people who are members of this community. Understanding Lontara lay letters through puzzle and braille media is a pioneer and activator for the visually impaired to inspire the community and all Indonesian people that as a nation it should be a shared responsibility to uphold the values of local wisdom by using local languages. The application of puzzle games can also improve children's motor skills and creativity skills